2016
DOI: 10.4414/smw.2016.14323
|View full text |Cite
|
Sign up to set email alerts
|

High blood pressure: prevalence and adherence to guidelines in a population-based cohort

Abstract: There is room for improvement in managing hypertension in Switzerland. Population-based observational studies are essential for identifying and evaluating unmet needs in healthcare; however, to pinpoint the underlying causes it is imperative to facilitate linkage of cohort data to medical records.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 16 publications
3
17
0
Order By: Relevance
“…One-third (35.4%) of participants was excluded at baseline due to hypertension. This prevalence is almost identical to the one found in the Bus Santé study of Geneva (34.4%) 16 and in another multi-cantonal cohort study (34.9%) 17 . Overall, the prevalence of hypertension in our sample agrees with other existing data for Switzerland.…”
Section: Prevalence Of Hypertensionsupporting
confidence: 86%
“…One-third (35.4%) of participants was excluded at baseline due to hypertension. This prevalence is almost identical to the one found in the Bus Santé study of Geneva (34.4%) 16 and in another multi-cantonal cohort study (34.9%) 17 . Overall, the prevalence of hypertension in our sample agrees with other existing data for Switzerland.…”
Section: Prevalence Of Hypertensionsupporting
confidence: 86%
“…Even in high-income countries such as Switzerland, the rate of BP control in hypertensive patients is 40.8%, and nonadherence with treatment is high. 5 Improving HTN management by strategies that are feasible in typical health care settings is essential.…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension (HTN) is a cardiovascular syndrome characterized by continuous elevation of arterial blood pressure, which is one of the major risk factors and main death causes of cardiovascular diseases. [ 1 ] Cardiovascular Disease Report in China has shown that the mortality rate of cardiovascular diseases ranks the first among all kinds of diseases, higher than cancers and other diseases. Hypertension is considered as an important public health problem in developed and developing countries.…”
Section: Introductionmentioning
confidence: 99%